Evaluation of efficacy, safety and cost of oral and parenteral iron preparations in patients with iron deficiency anemia - Pavan Jagdishbhai Panchal, Mira Kiranbhai Desai, Samidh P Shah, Manish N Solanki (Journal of Applied Pharmaceutical Science, 2015)
Objective: To compare the efficacy and safety of different oral and parenteral iron preparations in patients with anemia.Methods: An observational, prospective study in patients of anemia in pregnancy and chronic kidney disease (CKD) receiving iron sucrose, oral ferrous ascorbate and ferrous sulfate were included. Demographic details, clinical history, baseline hemoglobin, anemia indices data were recorded in a case record form. The patients were followed up monthly for 12 weeks and observed for clinical and haematological improvement and adverse drug reactions (ADRs). The data was analyzed using paired t-test, unpaired t-test and Fisher`s exact test.Results: Out of 232 patients, 84 received iron sucrose, 62 ferrous ascorbate and 86 ferrous sulfate. Oral and parenteral iron preparations significantly (P
Keywords: Anemia in pregnancy, chronic kidney disease, parenteral iron sucrose, oral ferrous ascorbate, oral ferrous sulfate.